Mapping The Worldwide Knowledge of Jack Bean by A Bibliometric Approach - Fitriani, Aprilia; Onyeaka, Helen; Agustia, Friska Citra (Universitas Ahmad Dahlan, 2024)
Indonesia's indigenous inhabitants acknowledge the local legume plant known as jack bean. The Jack bean has various advantages, including increased production, a shorter lifespan, upright stems mimicking shrubs, and improved tolerance to biotic and abiotic stresses. Nonetheless, the jack bean plant is particularly vulnerable due to harmful compounds such as canavaline, choline, hydroziamine acid, trogonelin, and cyanide. A bibliometric study was performed to locate studies on jack beans. The data collection procedure includes executing an extensive search in Scopus-indexed journals using the keywords